Tinjauan harmoni dalam lagu "Home" karya Andrew York - indra sakti prahasta (Repertoar, 2020)
Home is a song full of harmonious tones with melancholy nuances. To be able to play a song that is full of harmonization, there are several harmony sciences that need to be mastered including understanding the structure and form of the song, understanding the harmony found in the song such as chord progressions and the types of harmony used. The purpose of this study is (1) to find out the chord progression in the Home song, (2) to find out the types of harmony in the Home song. Research location in the city of Surabaya, East Java, with the research object Home song. The data collection technique used is active participation observation. Data analysis techniques used are editing, coding, and tabulation. Based on the results of this study it can be seen that the song Home has three parts namely A1-A2-B-C, with sentences that are repeated in certain parts. There are mixed chord progressions such as regular chord progressions and unusual chord progressions, and there are 5 types of harmony in this song and several inversions in several sentences in the Home song.Keywords : Harmony, Chord progression